(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This review focuses on the power quality assessment of distributed generation (DG) systems with an emphasis on adaptive voltage control. As the integration of renewable energy sources into power grids increases, maintaining voltage stability and ensuring power quality become critical challenges. Adaptive voltage control methods have emerged as effective solutions to mitigate issues such as voltage sags, swells, and harmonic distortions. This paper examines various adaptive voltage control strategies, their impact on power quality, and the associated benefits and limitations. The review highlights recent advancements, providing insights into optimizing DG systems for improved reliability and efficiency.